Ilqo’; Strategi Peningkatan Keterampilan Berbicara Di Pondok Pesantren Salafiyah Syafi’iyah - Aisyatul Hanun (Universitas Yudharta Pasuruan, 2019)
This research is based on increasing the Santri’s interest in learning Arabic language in Islamic Boarding School of Salafiyah Syafiiyah Sukorejo Situbondo. It can be seen from various dorm areas which have been designed a particular room to learn Arabic even almost every complex. However, each complex has a different learning strategy. so, the effect on learning resultwill be different. Based on perceptions from different sides, learning Arabic in syafahiyah is not as easy as learning Arabic theories “nahwu-sharraf”. Meanwhile, Islamic boarding school environment that tends to use the classic system, learn more Arabic to comprehend classic books. For this reason, it is necessary to accentuate the purpose of every learning process. In learning maharah al-kalam that was held in Salafiyah Syafi'iyah Sukorejo Situbondo boarding school, that is El-Marwah community used “ilqa strategy” to make students easier to apply vocabulary which has been memorized everyday and get more newmufrodat in every discussion process, in addition students are more confident to communicate in Arabic.